Repetitions, duration and intensity of upper limb practice following the implementation of robot assisted therapy with sub-acute stroke survivors: an observational study. (18th August 2022) - Flynn, Nicholas; Froude, Elspeth; Cooke, Deirdre; Kuys, Suzanne
Abstract: Background: Robot assisted upper limb (UL) therapy has been identified as an intervention with the potential to help improve the amount of practice performed by stroke survivors. Objectives: This study aimed to measure the amount of UL practice (i.e., repetitions, duration, intensity) performed by subacute stroke survivors, in particular those with severe UL impairment, pre and post implementation of robot assisted upper limb therapy (RT-UL) into an inpatient rehabilitation setting. Methods: Two observational study phases (pre-RT-UL and post-RT-UL) were undertaken of occupational therapy and physiotherapy sessions performed by subacute stroke survivors. Upper limb tasks observed and recorded in therapy were classified as either impairment-related therapy or activity-related. Results: In the pre-RT-UL observational phase, 7 subacute stroke survivors were observed across 11 days involving 25 therapy sessions. Post-RT-UL, 12 subacute stroke survivors were observed across 12 days involving 29 therapy sessions. There were no significant differences in characteristics of patients observed in each phase ( p > .05). The mean difference (95% CI) between pre and post RT-UL for repetitions (reps) (569 (1 to 1136) and intensity (7 (4–11)) reps/min of practice increased for all patients, including those with severe UL impairment (337 (37–638)) reps and 8 (2–14) reps/minute, with the duration of therapy unchanged. Conclusions: This is the first study to have observed an increase in UL practice with the inclusion of RT-UL as part of routine clinical practice. This increase in practice is considered to be due to RT-UL providing highly supportive and expeditious semi-supervised practice. Notably, RT-UL was able to be implemented within the existing organisational structures with only basic training of therapy staff. IMPLICATIONS FOR REHABILITATION: Robotics presents as a viable intervention to increase the amount and intensity of upper limb practice performed by stroke survivors in routine clinical practice Robotics were able to be implemented within the existing organisational structures with only basic training of therapy staff